2001
DOI: 10.1182/blood.v97.10.3205
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms of folate- and methionine-metabolizing enzymes and susceptibility to malignant lymphoma

Abstract: Genetic alteration is considered a probable cause of malignant lymphoma. Folate and methionine metabolism play essential roles in DNA synthesis and DNA methylation, and their metabolic pathways might thus affect disease susceptibility. In the present study, 2 polymorphisms were evaluated for a folate metabolic enzyme, methylenetetrahydrofolate reductase (MTHFR), and one was evaluated for methionine synthase (MS). The 2 polymorphisms, MTHFR677 C3T and MTHFR1298 A3C, are reported to reduce the enzyme activity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
123
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 29 publications
16
123
3
1
Order By: Relevance
“…Methionine synthase (MS) catalyzes the transfer of a methyl group from 5-methyl THF to homocysteine, which produces methionine and THF [13]. A common polymorphism at position 2756 within the MTR gene (A2756G, rs1805087) results in a transition from adenine to guanine that was thought to be associated with enzyme activity [14]. MTRR catalyzes the reductive methylation of MS using S-adenosylmethionine providing the methyl group, and may also participate in DNA methylation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Methionine synthase (MS) catalyzes the transfer of a methyl group from 5-methyl THF to homocysteine, which produces methionine and THF [13]. A common polymorphism at position 2756 within the MTR gene (A2756G, rs1805087) results in a transition from adenine to guanine that was thought to be associated with enzyme activity [14]. MTRR catalyzes the reductive methylation of MS using S-adenosylmethionine providing the methyl group, and may also participate in DNA methylation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Primers were for each polymorphism as follows. The primers of MTR A2756G were forward 5'-TGTTCCAGACAGTTA-GATGAAAATC-3' and reverse 5'-GATCCAAAGC-CTTTTACACTCCTC-3' [16]. The cycling conditions were 94°C, 30 s; 57°C, 30 s; 72°C, 60 s (35 cycle).…”
Section: Genotypingmentioning
confidence: 99%
“…2 A common polymorphism in methionine synthase (MTR) gene (2756A-G, rs1805087) was initially thought to be associated with lower enzyme activity than MTR 2756AA genotype, causing homocysteine elevation and DNA hypomethylation. 3 However, in subsequent investigations, some studies suggested a modest inverse association between 2756GG polymorphism and homocysteine levels, indicating an increased enzymatic activity of the variant genotype. 4 Moreover, Paz et al 5 found that individuals who carried 2756GG showed a lower frequency of CpG island hypermethylation in tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%